جودة الحياة و علاقتها بالتكيف الاجتماعي لدى الطالبات المقيمات بالحي الجامعي دراسة ميدانية بالاقامة الجامعية بج بمدينة الأغواط - سميحة عكيف; فايزة عبد العالي; شلالي لخضر (My University, 2018)
The current study aimed to know the relationship between the quality of life of social adjustment and to determine the level of each of the variables to the university students residing in the district, as well as reveal the differences in the quality of life social adjustment depending on the variant of seniority in the duration of the university accommodation. The study sample consisted of (80)student university district (Sisters(followed The two researchers clearly from the descriptive approach. He used all of the measure of quality of life (preparation of SHAHER IMMORTALIZED Solomon, 2010. The measurement of social adjustment, (preparation of nawaf Abdullah, 1978 *where the results of the study as follows: -1University students residing in the district to a low in the quality of life. .2The University students residing in the district in the low degree of social adjustment. .3There are differences between the students in quality of life, depending on the seniority in the university district. .4There are differences between the students in the social adjustment depending on the seniority in the university district. .5There is a correlation between life social adjustment to the university students residing in the district.quality of life - social adjustment